INNOVATIVE APPROACHES TO INCREASING THE EFFECTIVENESS OF RAILWAY TRANSPORT SERVICES IN UZBEKISTAN - Utepbergenov Allambergen (Modern American Journals, 2025)
The efficiency of transport services plays a pivotal role in ensuring sustainable economic growth and competitiveness in developing countries. This paper examines the prospective directions for enhancing the efficiency of services in the transport sector of Uzbekistan, with a focus on Uzbekistan Railways JSC. The research employs theoretical analysis, comparative methods, and econometric assessment of key indicators to identify challenges and policy solutions. Findings reveal that the digitalization of transport management, implementation of energy-saving technologies, and improvement of public–private partnership (PPP) mechanisms are crucial to raising the efficiency of transport services. Recommendations are developed based on recent presidential decrees and national programs for 2022–2030, aligning with the strategic objectives of the New Uzbekistan Development Strategy. The study contributes to the scientific discourse on service economy (08.00.05) and provides policy guidance for future reforms.
Keywords: Transport services, efficiency, innovation, Uzbekistan Railways, digitalization, economic development.